Sintesis Membran Silika Kitosan Dari Abu Ampas Tebu (Bagasse) - Sjamsiah Sjamsiah; Kurnia Ramadani; Hermawan Hermawan (Study Program of Chemistry - Alauddin State Islamic University of Makassar, 2017)
Membrane is a polymer layer that can be used in the process adsorbsi metal ions. Membrane can be synthesized from silica dust bagasse that termodifikasi kitosan. The purpose of this research is to know the impact of the addition of a variety of silicate on the characteristics of the membrane silika-kitosan the bagasse to the adsorpsi metal ions Pb. The content of silica in the bagasse to 73, 80 %. Membrane kitosan-silika be made with different variations of the composition of which is 1 : 1 ; 1 : 1, 5 ; 1 : 2 ; 1 : 2, 5 and 1 : 3 and the ability of the adsorpsi the metal Pb in a row of 41 %, 43, 76 %, 54, 88 %, 38, 36 % and 39, 6 %.. The application of membrane to the process adsorpsi metal ions Pb by membrane said with a ratio of 1 : 2 to concentrate Pb the beginning of the 50 parts per million. The use of membrane to the process readsorpsi to do with how to choose a membrane that has the adsorpsi of the membrane with a ratio of 1:2 be able to absorb metal Pb of 1 ppm. Membrane that has been used can be used with traffic readsorpsi, 2 % in the membrane of every 1 : 2.